Vein rupture by Arrow-Trerotola percutaneous thrombolytic device in a treatment of thrombosed arteriovenous graft. Issue 4 (July 2018) - Hong, Yong Kook; Kang, Kyung Hoon; Kim, Tae Hwan; Yang, Hee Chul
Introduction: We report a case of vein rupture by Arrow-Trerotola percutaneous thrombolytic device (Trerotola PTD) during a treatment of thrombosed arteriovenous graft (AVG). Case Description: A 77-year-old woman with a problem of thrombosed AVG underwent an endovascular treatment including a procedure of angioplasty of axillary vein. After angioplasty of axillary vein, we found a newly developed thrombus in axillary vein and performed thrombolysis using an over-the-wire 7F Trerotola PTD. When the rotating cage of the device arrived at axillary vein, it suddenly stopped, fixed at the angioplasty site, and didn't move at all. Venogram showed an extravasation of contrast media at axillary vein, suggesting vein rupture. The patient underwent an emergency operation. Conclusions: It could be dangerous to use Trerotola PTD in a native vein immediately after angioplasty.